A High-Efficiency Compact Planar Antenna for ISM Wireless Systems - Tao Zhou; Yazi Cao; Zhiqun Cheng; Martine Le Berre; Francis Calmon (International Journal of Antennas and Propagation)
A novel high-efficiency compact planar antenna at 433 MHz with minimized size and low-cost and easy to integrate into the ISM wireless applications is designed, fabricated, and measured. Capacitive strips that are formed by cutting inter-digital slots and the meander lines on both sides are introduced to greatly reduce the antenna size yet maintain the high efficiency. The proposed antenna has a simple planar structure and occupies a small area (i.e., 45 × 30 mm2). This novel electrically small antenna can be operated well without any lumped elements for impedance matching. Details of the antenna design and experimental results are presented and discussed.